IMPLEMENTASI PENDEKATAN MEANINGFUL LEARNING BERBASIS METODE ROLE PLAYING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD - Muhammad Febriandi; Dhea Adela (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low achievement of students’ learning outcomes in the IPAS (Science and Social Studies) subject at the elementary school level is the main issue addressed in this study. This condition is closely related to the continued dominance of conventional teaching methods, which tend to be monotonous and lack relevance to students’ daily lives. As a result, students struggle to understand concepts, are less engaged in discussions, and show low learning interest. To address this problem, a preliminary study was conducted through classroom observations and interviews with teachers and students, and was further strengthened by a literature review to obtain a more comprehensive perspective. The findings revealed that the meaningful learning approach based on the role playing method had not yet been implemented in the school. Based on the results obtained, this approach shows significant potential to improve students’ learning outcomes and is deemed a promising alternative for creating innovative and enjoyable learning experiences in elementary education. Given the urgency of improving the quality of learning, this approach needs to be tested directly so that its benefits can be measured scientifically.